The Enhancing Teacher Competency Program for Learning Management of 4 MAT Learning Cycle under the Roi Et Primary Educational Service Area Office 3 - Sukkorn, Suttinee; Thummatasananon, Sutum (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2021)
The objective of the research article were 1) to study current, desirable conditions and needs for learning management of 4 MAT learning cycle, 2) to develop the enhancing teacher competency program for learning management of 4 MAT learning cycle under the Roi Et Primary Educational Service Area Office 3. The sample consisted of 335 teachers under Roi Et Primary Educational Service Area Office 3. The semi-structured interview was 6 teachers. The research instruments were semi-structured interview, focus group discussion and appropriateness and feasibility assessment of the program. The frequency, percentage, means, standard deviation and Modified Priority Needs Index were employed to analyze data. The findings of this research were as follows: 1. The overall of current condition for learning management of 4 MAT learning cycle was at high level, the needs to enhance teacher competency for learning management of 4 MAT learning cycle under the Roi Et Primary Educational Service Area Office 3 by ranking from maximum to minimum following 1) concept construction development 2) framework performance 3) experience sharing 4) creating experience 5) creating task 6) task analysis. 2. The enhancing teacher competency program for learning management of 4 MAT learning cycle under the Roi Et Primary Educational Service Area Office 3 composed of 1) principle, 2) objective, 3)content and activities, 4) development process which included self-directed learning, action learning and attendance training and seminar, 5) program evaluation. The overall of the assessment of learning management of 4 MAT learning cycle under the Roi Et Primary Educational Service Area Office 3 in term of appropriateness was at high level and possibility was at highest level.